2018
DOI: 10.1002/ece3.3724
|View full text |Cite
|
Sign up to set email alerts
|

The description and number of undiscovered mammal species

Abstract: Global species counts are a key measure of biodiversity and associated metrics of conservation. It is both scientifically and practically important to know how many species exist, how many undescribed species remain, and where they are found. We modify a model for the number of undescribed species using species description data and incorporating taxonomic information. We assume a Poisson distribution for the number of species described in an interval and use maximum likelihood to estimate parameter values of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Specifically, the prevalence of ebolaviruses circulating in populations of putative hosts, such as bats, can vary greatly across short periods of time (116) and is often lower (118) than prevalences observed in other viruses whose hosts have been identified more rapidly with the aid of voucher specimens (see the "Hantaviruses" section above). Furthermore, for mammals, the most targeted ebolavirus hosts thus far, the Afrotropics represents a hot spot of evolutionary diversity, with one recent study predicting at least 122 undiscovered species (121). Moreover, recent phylogenetic research using voucher specimens from natural history collections has indicated high levels of cryptic diversity in Miniopterus (122), a bat genus speculated to be a reservoir host for Zaire ebolavirus (123).…”
Section: Role Of Natural History Collections In Host-pathogen Researchmentioning
confidence: 99%
“…Specifically, the prevalence of ebolaviruses circulating in populations of putative hosts, such as bats, can vary greatly across short periods of time (116) and is often lower (118) than prevalences observed in other viruses whose hosts have been identified more rapidly with the aid of voucher specimens (see the "Hantaviruses" section above). Furthermore, for mammals, the most targeted ebolavirus hosts thus far, the Afrotropics represents a hot spot of evolutionary diversity, with one recent study predicting at least 122 undiscovered species (121). Moreover, recent phylogenetic research using voucher specimens from natural history collections has indicated high levels of cryptic diversity in Miniopterus (122), a bat genus speculated to be a reservoir host for Zaire ebolavirus (123).…”
Section: Role Of Natural History Collections In Host-pathogen Researchmentioning
confidence: 99%
“…Therefore, the interpretation of these results should be made with caution. To reduce the uncertainties inherent in these analyses, more recent methods incorporate the number of taxonomists who described species within a given time interval to account for taxonomic effort in the models and capture temporal variations in the description of new species (Fisher et al., 2018; Joppa et al., 2011; Lu & He, 2017). Despite the abovementioned issues, estimates of the number of undescribed species are important because many species may go extinct before they are even described (Mora et al., 2013; Tedesco et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the abovementioned issues, estimates of the number of undescribed species are important because many species may go extinct before they are even described (Mora et al., 2013; Tedesco et al., 2014). Combining these estimates with the spatial distribution of the probability of discovering new species is important for determining where and in which groups taxonomic efforts should be applied (Fisher et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These concerns have been expressed for nematodes, particularly the plant parasites (luc et al 1987, Maggenti 1991, 1988, as well as in some charismatic vertebrate groups like birds, amphibians and mammals. In primates, the number of species has doubled since 1985 through elevation of subspecies to species level even though few new taxa have been discovered (Burgin et al 2018, Fisher et al 2018, Isaac et al 2004. Taxonomic inflation may be less of an issue for nematodes than for more charismatic groups because new species have been overwhelmingly based on new material rather than just revision of old material as with primates.…”
Section: The Number Of Nematode Speciesmentioning
confidence: 99%